Quantum Data Compression for Efficient Generation of Control Pulses - Volya, Daniel; Mishra, Prabhat (2023 28th Asia and South Pacific Design Automation Conference (ASP-DAC), 2023)
In order to physically realize a robust quantum gate, a specifically tailored laser pulse needs to be derived via strategies such as quantum optimal control. Unfortunately, such strategies face exponential complexity with quantum system size and become infeasible even for moderate-sized quantum circuits. In this paper, we propose an automated framework for effective utilization of these quantum resources. Specifically, this paper makes three important contributions. First, we utilize an effective combination of register compression and dimensionality reduction to reduce the area of a quantum circuit. Next, due to the properties of an autoencoder, the compressed gates produced are robust even in the presence of noise. Finally, our proposed compression reduces the computation time of quantum control. Experimental evaluation using popular quantum algorithms demonstrates that our proposed approach can enable efficient generation of noise-resilient control pulses while state-of-the-art fails to handle large-scale quantum systems.